2022
DOI: 10.1002/jsp2.1187
|View full text |Cite
|
Sign up to set email alerts
|

Injectable decellularized nucleus pulposus tissue exhibits neuroinhibitory properties

Abstract: Background Chronic low back pain (LBP) is a leading cause of disability, but treatments for LBP are limited. Degeneration of the intervertebral disc due to loss of neuroinhibitory sulfated glycosaminoglycans (sGAGs) allows nerves from dorsal root ganglia to grow into the core of the disc. Treatment with a decellularized tissue hydrogel that contains sGAGs may inhibit nerve growth and prevent disc‐associated LBP. Methods A protocol to decellularize porcine nucleus pulposus (NP) was adapted from previous methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“…Epitopes of Galα1-3-Galβ1-(3)­4GlcNAc-R (α-Gal) are an important point in tissue transplantation, as they may be recognized by antibodies within the body, leading to graft rejection, but also remodeling . However, recent studies suggest a lack of α-Gal within the porcine NP . Thus, in this study, we chose to first focus on the removal of DNA to prevent transmission of endogenous viruses.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…Epitopes of Galα1-3-Galβ1-(3)­4GlcNAc-R (α-Gal) are an important point in tissue transplantation, as they may be recognized by antibodies within the body, leading to graft rejection, but also remodeling . However, recent studies suggest a lack of α-Gal within the porcine NP . Thus, in this study, we chose to first focus on the removal of DNA to prevent transmission of endogenous viruses.…”
Section: Introductionsupporting
confidence: 85%
“…To this end, we restricted the buffer volume to 0.01 mL/mg of tissue dry weight, effectively creating an incompletely swollen gel during the decellularization process. Similar to a recent previously published protocol, , with our protocol, overall GAG and collagen content were not of statistically significant difference with decellularization despite differences in median values. A high GAG/collagen ratio of ≈27 ± 5 is characteristic for NCM and was only slightly reduced in dNCM to ≈21.3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that cross-linking chondroitin sulfate or type I collagen in dECM hydrogels provides mechanical properties similar to those of normal NP tissue. 142,151 It is evident from numerous studies that to obtain dECM hydrogels with better mechanical properties, cross-linking polymers are required in addition to conventional gelling methods; the most common is the natural biological cross-linker genipin, although high concentrations of genipin may affect cellular activity. One of the most important aspects of future research is to find a cross-linking agent that has good mechanical properties and is nontoxic.…”
Section: Application Of Decm In Iddmentioning
confidence: 99%
“…To fabricate ECM-derived bioscaffolds, decellularization techniques have been developed to remove immunogenic cellular components from tissues, while striving to preserve the native ultrastructure and cell-instructive biochemical composition of the ECM ( Crapo et al, 2011 ). Various groups have reported NP decellularization protocols that can extract cellular content to obtain scaffolds enriched in structural ECM components ( Wachs et al, 2017 ; Piening et al, 2022 ; Illien-Jünger et al, 2016 ; Mercuri, Gill, and Simionescu 2011 ; Fernandez et al, 2016 ; Xu et al, 2019 ; Chan et al, 2013 ). Despite its low cellularity, decellularization of the NP is challenging because it contains a high concentration of GAGs that are more easily extracted during processing as compared to highly crosslinked collagens ( Tsuchiya et al, 2014 ; Peloso et al, 2016 ; Hanai et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%